Herpes zoster vaccine (Zostavax®): Cellulitic injection site reaction or bacterial cellulitis? - Ian F. Cook (Taylor & Francis Group, 2017)
A 70 y old woman presented with a cellulitic reaction following Zostavax® injection. This reaction could be differentiated from bacterial cellulitis on the basis of the temporal relationship between vaccination and onset of the reaction, its non progression and unresponsiveness to antibiotic therapy. Alerting health care providers to this type of reaction, also seen with pneumococcal and pertussis containing vaccines, should avoid the inappropriate use of antibiotics.